PROBLEM ASPECTS OF ATTRACTING FOREIGN INVESTMENT TO ECONOMY OF UKRAINE: CURRENT CHALLENGES - Matskiv , V.V. (The actual problems of regional economy development, 2017)
In the article the problematic aspects of foreign investment were investigated. The importance of investment regulation within the provision of investment security of country was proved. The dynamics of the investment were analyzed and investment security threats were estimated. The main unreasonable investment policy negative factors and ways of reduction of their impact were defined. The necessity of revision of public investment policy for overcoming deformation in the structure of the economy was grounded and suggestions of elimination of investment security threats were provided.